Clinical and quantitative computed tomography predictors of response to endobronchial lung volume reduction therapy using coils - Kontogianni, Konstantina; Eberhardt, Ralf; Schuhmann, Maren; Heußel, Claus Peter; Herth, Felix; Gompelmann, Daniela (The International journal of chronic obstructive pulmonary disease, 2018)
Clinical and quantitative computed tomography predictors of response to endobronchial lung volume reduction therapy using coils  Konstantina Kontogianni,1,2 Kanoe Russell,3 Ralf Eberhardt,1,2 Maren Schuhmann,1,2 Claus Peter Heussel,2,4 Susan Wood,3 Felix JF Herth,1,2 Daniela Gompelmann1,2 1Department of Pulmonology and Respiratory Care Medicine, Thoraxklinik at the University of Heidelberg, Heidelberg, Germany; 2Translational Lung Research Center Heidelberg, Member of the German Center for Lung Research DZL, Heidelberg, Germany; 3VIDA Diagnostics, Coralville, IA, USA; 4Diagnostic and Interventional Radiology with Nuclear Medicine, Chest Clinic (Thoraxklinik), University of Heidelberg, Heidelberg, Germany Objectives: Bronchoscopic lung volume reduction using coils (LVRC) is a well-known treatment option for severe emphysema. The purpose of this study was to identify quantitative computed tomography (QCT) and clinical parameters associated with positive treatment outcome.Patients and methods: The CT scans, pulmonary function tests (PFT), and 6-minute walk test (6-MWT) data were collected from 72 patients with advanced emphysema prior to and at 3 months after LVRC treatment. The procedure involved placing 10 coils unilaterally. Various QCT parameters were derived using Apollo imaging software (VIDA). Independent predictors of clinically relevant outcome (∆6-MWT ≥ 26 m, ∆FEV1 ≥ 12%, ∆RV ≥ 10%) were identified through stepwise linear regression analysis.Results: The response outcome for ∆6-MWT, for ∆FEV1 and for ∆RV was met by 55%, 32% and 42%, respectively. For ∆6-MWT ≥ 26 m a lower baseline 6-MWT (p = 0.0003) and a larger standard deviation (SD) of low attenuation cluster (LAC) sizes in peripheral regions of treated lung (p = 0.0037) were significantly associated with positive outcome. For ∆FEV1 ≥ 12%, lower baseline FEV1 (p = 0.02) and larger median LAC sizes in the central regions of treated lobe (p = 0.0018) were significant predictors of good response. For ∆RV ≥ 10% a greater baseline TLC (p = 0.0014) and a larger SD of LAC sizes in peripheral regions of treated lung (p = 0.007) tended to respond better.Conclusion: Patients with lower FEV1 and 6-MWT, with higher TLC and specific QCT characteristics responded more positively to LVRC treatment, suggesting a more targeted CT-based approach to patient selection could lead to greater efficacy in treatment response. Keywords: COPD, emphysema, interventional pulmonology, bronchoscopy, endoscopic lung volume reduction, endobronchial coils